Need Analysis for English Special Purpose in Medical Laboratory Technology Students - Nurhidayat Nurhidayat; Andi Fatmawati (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Abstract The process of learning for English Specific Purposes is not optimal because of planning in learning tha could not be relevant to the student's field of science. It is necessary to analyze the needs of students towards learning English with a special purpose. The purpose of this study was to see the students' needs for ESP learning. The object of this research was the students of the Medical Laboratory Technology Study Program, 2019/2020 academic year in Politeknik Kesehatan Muhammadiyah Makassar. This research used descriptive qualitative method. The data collecting techniques were questionnaires and interviews. Data were classified as student needs for learning English identified. The description of the results of student needs was used as a reference for planning the teaching materials.